PENERAPAN ARSITEKTUR ISLAM PADA REDESAIN PONDOK PESANTREN DARUL HUFFADH DI KABUPATEN BONE - Tulla, Rahmat Dwi Putra; Wasilah Sahabuddin; Irma Rahayu (The Department of Architecture, Faculty of Science and Technology, Universitas Islam negeri Alauddin Makassar, 2026)
Redesign is the activity of planning and redesigning a building so that physical changes occur without changing its function, either through expansion, changes or moving locations (John M). Darul Huffadh Tuju-Tuju Islamic Boarding School is one of the Islamic boarding schools in Bone Regency, Bone Regency is one of the regions in South Sulawesi Province, Indonesia. Islamic architecture is a form of unity between human culture and the process of human devotion to God, which is in harmony with the relationship between humans, the environment and the Creator. Islamic architecture reveals complex geometric relationships, hierarchies of forms and ornaments, and deep symbolic meanings. The redesign of the Darul Huffadh Tuju-Tuju Islamic Boarding School was based on various considerations, apart from the number of classes which was not possible for the students, also the function of the building which was not as it should be and the physical condition of several buildings which were no longer suitable for use. The application of Islamic Architecture in the Redesign of Islamic Boarding Schools is due to the similarity in efforts to restore and implement Islamic values in various physical and metaphysical aspects of the building through the concept of Islamic thought which makes the building show more Islamic nuances in the interior and exterior of the building, such as: a. the use of roster materials in buildings. b. addition of natural stone with calligraphic relief, use of geometry. c. the use of calligraphy both interior and exterior in buildings, choosing natural colors that are synonymous with a peaceful and beautiful atmosphere.